Effect of various inhibitors on the production of myo-inositol-1-phosphate synthase in Neurospora crassa wild-type strain - A. Kiss; A. Zsindely; M. Schablik; G. Szabo (Fungal Genetics Reports, 1985)
Effect of various inhibitors on the production of myo-inositol-1-phosphate synthase in Neurospora crassa wild-type strain